Halifax 1940 : port de transit pour l’or européen - de Lavigne-Aubery, Marie (The Northern Mariner / Le marin du nord, 2018)
Europe had been invaded and Britain stood alone to face Hitler’s armies. As it was imperative that the gold reserves in Europe’s central banks be protected from German greed, the gold had to be sent to North America in warships. With access to US ports limited by the Convention on maritime neutrality, the Allies chose the port of Halifax, Nova Scotia, as a transit hub for the European treasure. The gold was unloaded in the utmost secrecy and transported by rail to the Bank of Canada in Ottawa and the Federal Reserve in New York.